Distribution characteristics of soil AM fungi community in soft sandstone area. (15th August 2022) - Guo, Yangnan; Zhang, Huandi; Bao, Yuying; Tan, Houzhang; Liu, Xianghong; Rahman, Zia ur
Abstract: To explore the diversity and distribution characteristics of soil arbuscular mycorrhizae fungi (AMF) communities in the soft sandstone area, thirteen arsenic sandstone rock samples were collected from three planting plots (SI, SII and SIII) and one bare control plot (CK), separately. The sampling locations are as follows: the top of the slope (denoted by the number 1), sunny slope (2), shady slope (3) and gully bottom (4). These samples were then tested with an Illumina HiSeq PE250 high-throughput sequencing platform. Experimental results show that the SIII4 sample (from the gully bottom of the SIII plot) has the highest moisture content of 9.1%, while the CK sample in the control plot has lowest moisture content. SI2 has the highest pH of 9.58 and CK has the lowest pH of 8.73. SII1 has the highest available phosphorus (AP) content of 9.61 mg/kg, while SII3 has the lowest AP content of 2.29 mg/kg. Furthermore, SI2 has the highest NH4 –N content of 11.24 mg/kg, while SII1 has the lowest NH4 –N of 4.09 mg/kg. SII1 has the highest available potassium (AK) content of 48.92 mg/kg and CK has the lowest AK content of 1.82 mg/kg. In the observed-species index reflecting AMF genetic diversity, SI1 differences significantly from SII4 and SIII3 (P < 0.05). In the Shannon index, SI1 is significantly different from SI2, SI3, SI4; SII2 is significantly different from SII3; SI2, SI4, SII1 and SII3 are quite different from CK (P < 0.05). The dominant genera of AMF in these plots include Glomus (17.24%–65.53%), Scutellospora (0.04%–67.38%), Septoglomus (2.83%–43.03%) and Kamienskia (0.64%–46.38%). The dominant genera of AMF vary significantly between sunny slope and shady slope. Positive correlation exists between soil NH4 –N and the AM fungal community structure. There are prominent positive correlations exist among genetic diversity index chao1, observed-species, pH and AP (P < 0.05), and obviously negative correlation between observed species and AK (P < 0.05). The research findings on the distribution characteristics of AM fungus community in the arsenic sandstone plot and their relationship with environmental factors can help with arsenic sandstone management in other similar areas. Highlights: Alpha diversity of bacterial community was greater at the gully bottom and the shady slope. Soil pH and available phosphorus have significant influences on bacterial community structure. The fungi at sunny slope were different from that at the shady slope. Soil NH4 –N has a significant influence on the fungal community structure.